Comprehensive Review on Diabetes Associated Cardiovascular Complications - The Vitamin D Perspective - Durgarao, Y.; Manjrekar, Poornima A.; Adhikari, Prabha; Chakrapani, M.; Rukmini, M.S. (Cardiovascular & Haematological Disorders - Drug Targets, 2019)
Vitamin D, a steroid hormone is primarily known for its role in calcium and bone mineral homeostasis. Over the years, vitamin D has been implicated in various non-skeletal diseases. The extraskeletal phenomenon can be attributed to the presence of vitamin D receptors (VDRs) in almost all cells and identification of 1-α hydroxylase in extrarenal tissues. The vitamin D deficiency (VDD) pandemic was globally reported with increasing evidence and paralleled the prevalence of diabetes, obesity and cardiovascular diseases (CVDs). A dependent link was proposed between hypovitaminosis D glycemic status, insulin resistance and also the other major factors associated with type 2 diabetes leading to CVDs. Insulin resistance plays a central role in both type 2 diabetes and insulin resistance syndrome. These 2 disorders are associated with distinct etiologies including hypertension, atherogenic dyslipidemia, and significant vascular abnormalities that could lead to endothelial dysfunction. Evidence from randomised clinical trials and meta-analysis, however, yielded conflicting results. This review summarizes the role of vitamin D in the regulation of glucose homeostasis with an emphasis on insulin resistance, blood pressure, dyslipidaemia, endothelial dysfunction and related cardiovascular diseases and also underline the plausible mechanisms for all the documented effects.
Keywords: Vitamin D